How does the Philippines fare in meeting ASEAN economic community vision 2025? - Francis Mark A. Quimba; Maureen Ane D. Rosellon; Jean Clarisse T. Carlos (Philippine Institute for Development Studies (PIDS), 2020)
In November 2015, the ASEAN Community composed of three (3) pillars: the ASEAN Economic Community (AEC), the ASEAN Socio-Cultural Community (ASCC), and the ASEAN Political-Security Community (APSC) was established as a response by the ASEAN Member states to the need to develop a Post-2015 Vision of a cohesive, economically integrated, socially responsible and a truly people oriented, people -centered and rules-based ASEAN. Each pillar corresponds to a blueprint, and are part of the general master plan called ASEAN Community Vision 2025 with the theme "ASEAN 2025: Forging Ahead Together". This study focuses on the AEC Blueprint 2025 and its characteristics and elements. After five years upon establishment, there is a need to assess how the Philippines has fared in achieving the key result areas in the AEC Blueprint 2025. By comparing the baseline with the most recent data, this study found that the Philippines is among the middle of the pack (ranking from 4th to 6th) among the ASEAN countries. In terms of AEC vision and goals, the Philippines performance suggests that the country is generally on track and is progressing in the right direction.
Keywords: 330; ASEAN Economic Community; AEC; AEC Blueprint; ASEAN 2025